Acceptability and Nutritional Content of Barongko Substituted with Pumpkin as an Alternative to Traditional Snacks for Elementary School Children - Arsandhy. H, Muh. Alif; Ismawati, Rita (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Children of elementary school age (6-12 years) need balanced nutrition, including energy from carbohydrates, protein, fat, and vitamin A to support growth, activity, and cognitive development. This study develops barongko cake with a substitution of pumpkin to assess its acceptability and nutritional content as an alternative traditional snack for elementary school children. The aim of this study is to evaluate the acceptability of color, aroma, texture, and taste, as well as the energy, protein, fat, carbohydrate, and vitamin A content of barongko cake with pumpkin substitution. This study is an experimental research with a Completely Randomized Design. Data collection for hedonic tests was carried out on 43 panelists, consisting of 5 trained panelists and 38 semi-trained panelists, for three formulations developed, namely F1 (90% pumpkin and 10% banana kepok), F2 (80% pumpkin and 20% banana kepok), and F3 (70% pumpkin and 30% banana kepok), and then analyzed using the Kruskal-Wallis test and the Mann-Whitney test for further analysis. The results of the study from the three formulations showed an effect on the acceptability of color and aroma, but no effect on texture and taste. The best product was shown in F2. The nutritional content test results of the best barongko cake with pumpkin substitution or F2, based on laboratory tests, showed a nutritional content of 156.84 kcal for energy, 1.35 g of protein, 0.99 g of fat, 8.98 g of carbohydrates, and 69.83 RE of vitamin A, with contributions to the Recommended Daily Intake (RDI) requirements of 7.8-9.5% energy, 1.8-3.2% protein, 1.8-2.7% fat, 2.7-3.6% carbohydrates, and 11.6-13.9% vitamin A.